Business Evolution in Poland at The Time of Covid-19 Pandemic: Selected Issues - Miroslaw BETKOWSKI (Communications of International Proceedings, 2021)
The turn of 2019 and 2020 will be remembered in the history of the modern world as the time of the pandemic of COVID-19. The environment of changing reality recorded a new unknown phenomenon of the need to isolate entire societies. This caused various perturbations in the social, cultural and economic life of citizens. This phenomenon has had and continues to have a direct impact on business, which has had to redefine its management models. New forms of working, which had previously been in experimental phases, had to be accelerated and shaped into a new model of remote working. In this article, the author attempts to analyse and synthesise business activities in the area of the Pomerania Province (Pomorskie Region), located in Poland. By means of a questionnaire sent to businessmen associated in Słupsk Chamber of Industry and Commerce (Słupska Izba Przemysłowo-Handlowa) and the Chamber of Committed Business (Izba Zaangażowanego Biznesu), the author endeavours to present the condition of local business in the period of pandemic and the basic measures of handling a new reality.
Keywords: Pandemic; business of Pomerania Province; activity in pandemic